The Relationship Between Indonesian EFL Learners’ Vocabulary Knowledge and English Competencies - Hartini, Lintang Wilujeng; Suri Ardini, Anandayu (English Education Department, Universitas Islam Indonesia, 2024)
English vocabulary mastery is considered important in Indonesian education, but the actual vocabulary mastery of high school students is still below the target. It becomes a concern whether the low vocabulary knowledge is correlated with English skills. Thus, this study investigated the relationship between Indonesian students’ English vocabulary knowledge and English competencies. A total of 108 high school students completed a productive vocabulary test (Lex 30). The students’ scores from their English class served as the data for English competence. The Lex30 result and the English scores were then tested using Pearson correlation. The findings showed that the students’ vocabulary knowledge and English competencies had positive correlation. Despite no specific measurement of the vocabulary size from the lex30 score, it was relevant to measure students’ vocabulary knowledge required for their performance in general English skills (reading, writing, listening, and speaking). Thus, the positive correlation indicated that students with good vocabulary knowledge might also had good English scores. This study's specific contextual focus may restrict the applicability of the findings to other contexts. Therefore, future research should diversify the sample, incorporate a wider range of assessment tools, and explore the impact of different teaching methods on language skills in various settings.